A wonder book - Hawthorne, Nathaniel, 1804-1864.; Fell, Herbert Granville, b. 1872. (London : J.M. Dent & Sons ; New York : E.P. Dutton & Co.)
Adaptations of Greek Myths: The Gorgon's head, The golden touch, The three golden apples, The Chimera.
Mode of access: Internet.
Keywords: Mythology, Classical -- Juvenile literature